2021
DOI: 10.1111/and.14265
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed miRNAs and potential therapeutic targets for asthenospermia

Abstract: Infertility has become a globally important issue in reproductive health. Approximately 10%-15% of reproductive-aged couples worldwide are afflicted by infertility, which is attributable to men in approximately 50% of cases (Sabanegh, 2011). According to World Health Organization (WHO) guidelines, male infertility is defined as the inability to conceive after at least 12 months of regular, unprotected sexual intercourse (Zegers-Hochschild et al., 2009).Asthenozoospermia is detected in 40% of infertile men, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…When the above pathways were disturbed, the proliferation ability of SSCs (Lee et al, 2007;Yao et al, 2020) and Sertoli cell (Niu et al, 2015;Wang et al, 2015;Wang et al, 2017) would be inhibited. In addition, a study on asthenozoospermia population indicated that differentially expressed miRNAs in seminal plasma samples between patients with asthenospermia and healthy men were significantly associated with PI3K-Akt signaling pathway, MAPK signaling pathway and HIF-1 signaling pathway (Liang et al, 2022), which were consistent with our findings. Apart from that, the target genes of DE piRNAs were also significantly enriched in three pathways related to the cytoskeleton: Regulation of actin cytoskeleton, Chemokine signaling pathway and Focal adhesion pathway.…”
Section: Prediction Of Differentially Expressed Piwi-interacting Rna ...supporting
confidence: 91%
“…When the above pathways were disturbed, the proliferation ability of SSCs (Lee et al, 2007;Yao et al, 2020) and Sertoli cell (Niu et al, 2015;Wang et al, 2015;Wang et al, 2017) would be inhibited. In addition, a study on asthenozoospermia population indicated that differentially expressed miRNAs in seminal plasma samples between patients with asthenospermia and healthy men were significantly associated with PI3K-Akt signaling pathway, MAPK signaling pathway and HIF-1 signaling pathway (Liang et al, 2022), which were consistent with our findings. Apart from that, the target genes of DE piRNAs were also significantly enriched in three pathways related to the cytoskeleton: Regulation of actin cytoskeleton, Chemokine signaling pathway and Focal adhesion pathway.…”
Section: Prediction Of Differentially Expressed Piwi-interacting Rna ...supporting
confidence: 91%
“…There have been a number of reports about the participation of the FoxO signalling pathway and foxo genes in spermatogenesis in mammals. Among them, foxo1 is conserved in mammalian species and has been suggested to play an important role in spermatogonial stem differentiation and spermatogenesis [ 20 , 21 , 22 , 23 , 24 , 25 ]. We also analyzed the expression patterns of the five foxo genes in early gonadal stages, all of which showed male-biased expression (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include miR-10b-3p and miR-34b-5p, which could serve as predictive biomarkers of azoospermia, as well as miR-122-5p, which was found to be up-regulated in human spermatogonia from OA patients compared to NOA patients [66,97]. Human semen sample qPCR miR-34b-5p is down-regulated in patients with asthenozoospermia and oligozoospermia [93] Testicular tissue Microarray and validation with qRT-PCR 129 miRNAs were differentially expressed in the NOA group compared to control Combination of miR-10b-3p and miR-34b-5p as a predictive biomarker of azoospermia [97] Human male germ cells isolated from testicular tissue miRNA microarray miR-122-5p is up-regulated in human spermatogonia of patients with OA compared to NOA patients [66] Human seminal plasma High-throughput sequence technology and validation with RT-qPCR 6 miRNAs were up-regulated (miR-765, miR-5000-3p, miR-4289, miR-6514-3p, miR-6882-5p, miR-6739-5p) and 7 (miR-34b/c-5p, mR-135a-5p, miR-146b-5p, miR-196b-5p, miR-449a, miR-509-3p) were down-regulated in patients with asthenozoospermia compared to healthy men [95] Human seminal plasma and urine samples Next-generation sequencing 13 miRNAs differentially expressed (10 in seminal plasma samples and 3 in urine) to predict the presence of testicular spermatogonia [96] Cell culture Microarray Genetic screen miR-372 and miR-373: potential novel oncogenes in testicular germ cell tumors by interfering with p53 pathway [99] Testicular tissue qPCR miRNA expression profile to distinguish type II and III germ cell tumors [100] Improving the diagnosis of idiopathic male infertility with the help of molecular biomarkers combined with semen analysis and/or histopathologic diagnosis would be a major advancement in the field of male infertility management. MiRNAs appear to meet numerous requirements to be valuable biomarkers: they are present in various bodily fluids, they have been shown to be stable in seminal plasma [90], and appear prior to proteins and, thus, could aid the early detection of disease.…”
Section: Mirnas In Male Infertility and Their Use As Biomarkersmentioning
confidence: 95%
“…MiRNAs are also endogenous molecules that can be expressed in extracellular fluids and have been detected in seminal plasma, where their expression levels remain stable across multiple samples from the same individual [ 90 ]. Several studies have shown that miRNAs can be up- or down-regulated in human seminal plasma from patients with azoospermia, oligozoospermia, and asthenozoospermia [ 90 , 91 , 92 , 93 , 94 , 95 ]. Recently, miRNA expression patterns in urine and semen samples from non-obstructive azoospermia (NOA) patients were evaluated as potential biomarkers and proved to be effective for predicting the presence of testicular spermatozoa and spermatogonia before testicular sperm extraction (TESE) [ 96 ].…”
Section: Mirnas In Male Infertility and Their Use As Biomarkersmentioning
confidence: 99%